(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2022)
The purpose of this study was to see how self-directed dialogue affects the speaking ability of students at SMA LPP YW UMI Makassar. The self-directed dialogue technique is an activity that combines role-playing strategies or simulations with real means of communication or contextual practice. Self-directed dialogue supports students to use their sentences to generate discourse, this can be done with group learning, but the principle is that students are responsible for their learning. By using their sentences, students feel more understand what they want to build, because it is more familiar to them. Self-directed dialogue is a technique that can help students improve their speaking ability, there are 5 components of speaking skills related to comprehension, grammar, grammar, pronunciation, performance. Researchers used a pre-experimental approach with a one-group pre-test and post-test design, this study lasted for four weeks and included twelve meetings, including treatment. The number of samples was collected using a purposive sampling technique as many as 24 students in class X. The data were obtained using a speaking rubric which was then processed in SPSS v26. The results of the study found that the average score of students’ vocabulary development was 52.33 in the pre-test and 70.33 in the post-test. The students’ developing speaking ability is 34.39%. This is supported by the significance value of the t-test (0.00 < 0.05), from the statistical data it can be concluded that the alternative hypothesis is approved and the null hypothesis is rejected. Based on the findings, the researcher concludes that implementing self-directed dialogue can help class X students at SMA LPP YW UMI Makassar improve their speaking skills. This implies that self-directed dialogue is effective and influential in improving students’ speaking skills.